REKONSTRUKSI HUKUM PEMERINTAHAN DESA Pemikiran Perubahan Kebijakan Bagi Desa - KUSHANDAJANI, KUSHANDAJNAI (Politika: Jurnal Ilmu Politik, 2011)
AbstractThe existence of local autonomy regulation through the Law No. 32 of 2004, that regulatedistribution of authority between central government and the local government, has not givensomething meaningfully for prosperity of the village communities. The Law No. 32 of 2004 isambivalent. In one hand it recognize values of diversity, participation, indigenoese, democratization,and community development. On the other hand the authority to make decision making be in centralgovernment only. Law reconstruction is needed to reform village government and to encourageautonomy in village. It must be improve not only effectiveness of governance process but alsohumanitarian welfare of the village communities.Keywords: policy, local goverment, governance process, law reconstruction.